Mewujudkan Sekolah Literasi yang Berprestasi - Sabarudin Sabarudin (Society, 2018)
School culture is the most important factor in shaping students to be optimistic, brave, appearing, cooperative behavior, and personal and academic skills. To optimize the potential of students into an achievement, the right problem solving strategy was chosen, namely through the movement of literacy development to achieve Achievement. The main focus is to empower all school stakeholders in their daily activities by allocating existing educational resources to achieve the achievements and potential of students and realize the vision, mission and goals of the school. Optimizing the potential and achievements of students through the literacy movement can be done with three main principles, namely: (1) The development and strengthening of literacy becomes a movement and real action; (3) Establish communication and synergy with various parties; and (3) Building a shared commitment to optimize the potential and achievements of both academic and non-academic. Seriousness and strong will to make the development and strengthening of literacy as a "joint effort" by building a culture of literacy to prepare information literacy generation, literacy literacy generation, which will be an important component for optimizing the potential and achievement of students as large as must be based on noble goals in developing students' character through acculturing the school literacy ecosystem embodied in the School Literacy Movement (GLS).